Exploring effective maintenance strategies: a study of the relationships between nonprofits and college volunteers - Dong, Aobo (Kansas State University, 2011)
In the United States, the number of college-age students (19-24) who volunteer is rising rapidly. However, most of the research in regard to sustaining volunteers with nonprofits is targeted to the whole population, especially older adults. This research employed the first sample survey of college volunteers for the study of a public relations theory. The findings showed that theories developed for older adults may also apply to young adults and could provide insights about youth relationships. While using organization-public relationship model as the theoretical background, the results suggest that Access, Networking, and Assurance are important public relations strategies for nonprofits maintaining college volunteers. Nonprofits should try to cultivate a sense of commitment with college volunteers, which could greatly increase their volunteer intentions in the future. In addition, as suggested by the previous research, this study collected the data in regard to college volunteers' parents' social-economic status, and has found that parental involvement with nonprofits has a great impact on their children's volunteer behaviors in the future.
Keywords: non-profit organization; college volunteers; maintenance strategies; Communication (0459)